ANALISIS SWOT PENGGUNAAN DAPODIK PADA PENGELOLAAN DATA PENDIDIKAN DI SDN 010 BALIKPAPAN SELATAN - Saifullah El Afrinuddin Zain, Hanif; Sulfi Ardiansyah; Tri Wahyuni; Herlina; Ramadiani; Sudarman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of the Basic Education Data System (DAPODIK) in educational data management at SD Negeri 010 Balikpapan Selatan using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. This research employed a qualitative descriptive method with data collection techniques consisting of interviews, observations, and documentation. The research informants included the principal, school operators, teachers, and administrative staff. The results showed that the implementation of DAPODIK provides several strengths, including centralized data management, improved efficiency in digital-based administration, integration with the national education system, and support for data-driven decision-making. In addition, DAPODIK facilitates reporting processes and synchronization of educational data. However, the implementation still faces several weaknesses, such as dependence on internet connectivity, central server disruptions, student data validation problems, and a high dependence on the competence of school operators. Opportunities for DAPODIK development are supported by government policies on educational digitalization, operator training programs, and increasingly integrated educational information systems. Meanwhile, the threats identified include risks of national system disruptions, power outages, server overload during peak periods, and rapid policy changes related to the system. Based on the SWOT analysis, the implementation of DAPODIK at SD Negeri 010 Balikpapan Selatan is considered effective in supporting educational data management, although improvements in infrastructure and human resource capacity are still needed to optimize its implementation.